Let's solve the equation step by step and fill in the missing parts based on the operations applied to both sides.
Starting with the equation: \[ -2c + 20 - 14 = 10 \]
-
Combine like terms on the left-hand side:
- \( 20 - 14 = 6 \)
- So, we have: \[ -2c + 6 = 10 \]
-
Subtract 6 from both sides: \[ -2c + 6 - 6 = 10 - 6 \] \[ -2c = 4 \]
-
Divide both sides by -2: \[ \frac{-2c}{-2} = \frac{4}{-2} \] \[ c = -2 \]
Thus, the entire process in order with missing terms and descriptions filled is:
- Start with: \(-2c + 20 - 14 = 10\)
- Combine like terms
- Resulting in: \(-2c + 6 = 10\)
- Subtract 6 from both sides
- Resulting in: \(-2c = 4\)
- Divide both sides by -2
- Final result: \(c = -2\)
So, the final answer is:
- \(c = -2\)
- Divide both sides by -> -2
The answer is \(c = -2\).